2005
DOI: 10.1097/00001665-200501000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 45S5 Bioactive Glass Combined as a Bone Substitute in the Reconstruction of Critical Size Calvarial Defects in Rabbits

Abstract: Biomaterial research and tissue engineering have guided new developments in bone replacement. In this study, the osteoconductive and osteoinductive properties of 45S5 Bioglass (Novabone-C/M, Porex Surg., Newnan, GA), granules as a bone replacement material for large calvarial defects were evaluated. Rabbit periosteal cells were expanded in culture and used in vivo. Alkaline-phosphatase assay, collagen type I, and calcium expression were applied to confirm osteoblast phenotype. In the in vivo phase, a 15-mm dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
5
29
0
3
Order By: Relevance
“…Other studies randomized showed that there is glass on apatite-layer formation, rich in calcium and phosphorus, similar to natural bone, that favoring lead bone-glass (Stavropoulos et al, 2003) and inducing colonization of bone cells (Gatti et al, 2006). Bioactive glasses have been associated with other compounds such as demineralized bovine bone (Stavropoulos et al), autogenous bone graft (Tadjoedin et al, 2000(Tadjoedin et al, , 2002Moreira-Gonzalez et al), calcium phosphate (Moon et al, 2006), enamel matrix derivative (Kuru et al, 2006), and resorbable polymers composed of lactic acid and glycolic acid (Lu et al, 2003;Leach et al, 2006). Oonish et al (2000) studied, in animals, bioactive glass, Glass-ceramic A-W and synthetic hydroxyapatite and concluded that bioactive glass showed the highest bone formation rates and degradation, suggesting bone formation rates is proportional to particles dissolution, which favor the osteoblastics action.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies randomized showed that there is glass on apatite-layer formation, rich in calcium and phosphorus, similar to natural bone, that favoring lead bone-glass (Stavropoulos et al, 2003) and inducing colonization of bone cells (Gatti et al, 2006). Bioactive glasses have been associated with other compounds such as demineralized bovine bone (Stavropoulos et al), autogenous bone graft (Tadjoedin et al, 2000(Tadjoedin et al, , 2002Moreira-Gonzalez et al), calcium phosphate (Moon et al, 2006), enamel matrix derivative (Kuru et al, 2006), and resorbable polymers composed of lactic acid and glycolic acid (Lu et al, 2003;Leach et al, 2006). Oonish et al (2000) studied, in animals, bioactive glass, Glass-ceramic A-W and synthetic hydroxyapatite and concluded that bioactive glass showed the highest bone formation rates and degradation, suggesting bone formation rates is proportional to particles dissolution, which favor the osteoblastics action.…”
Section: Resultsmentioning
confidence: 99%
“…The migration of particles can degrade surrounding tissue in contact with surface and lead to an intense inflammatory reaction. The insertion of a resorbable material layer on the particles, keeping them in defect or mixing them with a material that causes their aggregation are two options mentioned by these authors in order to prevent the migrating of particles to the adjacent tissues (Moreira-Gonzalez et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In micro-computed tomography and histomorphometric comparison of two synthetic bone graft products using a rabbit posterolateral fusion model, Signafuse Bioactive Bone Graft Putty showed greater new bone formation than the Actifuse ABX sculptable synthetic bone graft substitute at 6 weeks post-surgery, but no further differences were detected at 12 weeks [31]. Despite the observation that the bioactive glass particles pack into a defect easily and stay in place, even when the site is bleeding in the periodontal treatment model, several studies report difficulties in keeping the bioactive glass particles within experimental defects [15,16,32]. Once the particles migrate, they start to degrade in the soft tissue and are associated with an intense inflammatory reaction [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated in in vivo preclinical studies that BAG particles do not stimulate bone formation if migrated into ectopic areas, such as soft tissues. This might lead to alterations in the internal structure of the BAG particles resulting in increase of the reaction surface that can be associated with a certain degree of inflammation in the surrounding soft tissue [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow cell culture systems with bioactive glass seem to be useful and induce osteogenic differentiation and cell mineralization . In another study, bioglass granules in combination with expanded periosteal cells in culture were investigated in rabbit large calvarial defects with increased ossification (Moreira-Gonzalez et al, 2005). Bioresorbable and bioactive tissue engineering composite scaffolds based on bioactive glass (45S5 Bioglass(R)) particles and macroporous poly(DL-lactide) (PDLLA) and polylactide-coglycolide (PLAGA) with osteoblasts (HOBs) cells have tremendous potential as scaffolds for guided bone regeneration (Roether et al, 2002;Lu et al, 2005;Yang et al, 2006;), for intervertebral disc tissue repair (Wilda & Gough, 2006;Helen & Gough, 2008).…”
Section: Bioactive Glasses' In Biomolecular Engineering With Special mentioning
confidence: 99%